2008
DOI: 10.1002/nau.20586
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamic parameters after solifenacin treatment in men with overactive bladder symptoms and detrusor underactivity

Abstract: Solifenacin treatment results in changes of urodynamic parameters. These changes, however, seem not to be of clinical significance as suggested by the lack of subjective deterioration in voiding difficulties and by the low incidence of AUR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 17 publications
0
13
1
Order By: Relevance
“…Ronchi et al. evaluated the efficacy of solifenacin 5 mg once daily in a non‐comparative prospective study of 49 men aged ≥ 40 years with OAB and urodynamically diagnosed detrusor underactivity (41). After 4 months, solifenacin significantly improved bladder diary variables and PPBC scores.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ronchi et al. evaluated the efficacy of solifenacin 5 mg once daily in a non‐comparative prospective study of 49 men aged ≥ 40 years with OAB and urodynamically diagnosed detrusor underactivity (41). After 4 months, solifenacin significantly improved bladder diary variables and PPBC scores.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are important because the storage symptoms that define OAB are common and bothersome in men and adversely affect HRQL, perhaps to a greater extent than voiding symptoms (12,52,53). Most of the evidence suggests that antimuscarinics alone can effectively treat OAB symptoms in men (13,29,(33)(34)(35)(36)38,41). However, tolterodine ER alone was not very effective in the general population of the TIMES study (19)(20)(21), which likely reflects the unique TIMES study population.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The changes of urodynamic parameters after solifenacin treatment in men with OAB and detrusor underactivity were reported 12 . The bladder contractility index (BCI) was significantly decreased after solifenacin treatment and this change showed that solifenacin decreased bladder contraction during the urine voiding phase.…”
Section: Discussionmentioning
confidence: 99%
“…As regards solifenacin, Tanaka et al [20] found a significant increase of bladder capacity and of PVR in female patients with OAB, but in this study data regarding the voiding phase of micturition have not been reported. Ronchi et al [21] found a significant decrease of the bladder contractility index after solifenacin treatment in men with OAB and detrusor underactivity; these data show that solifenacin decreases bladder contraction during the urine voiding phase [20], whereas no significant differences were found by Hsiao et al [22] in changes of Qmax and pdet.Qmax after solifenacin in female patients with OAB. As regards patients with outlet obstruction, mirabegron did not adversely affect the voiding function [23].…”
Section: Discussionmentioning
confidence: 97%